Heparins that block VEGF-A-mediated von Willebrand factor fiber generation are potent inhibitors of hematogenous but not lymphatic metastasis - Goertz, Lukas; Desch, Anna; Mayer, Frank Thomas; Nowak, Kai; Karampinis, Ioannis; Bohlmann, Michael K.; Umansky, Viktor; Bauer, Alexander (OncoTarget, 2016)
Von Willebrand factor (VWF) serves as a nidus for platelet aggregation and thrombosis. We hypothesize that VWF fibers contribute to the development of venous thromboembolism (VTE) and to metastasis formation. Here, we show that vascular and lymphatic endothelial cells (ECs) express VWF in vitro and release VWF fibers after activation by tumor cell supernatants. In contrast, an ex vivo analysis of primary mouse tumors revealed the presence of VWF fibers in the blood microvasculature but not in lymphatic vessels. Unlike the anticoagulant Fondaparinux, an inhibitor of thrombin generation, the low-molecular-weight heparin (LMWH) Tinzaparin inhibited VWF fiber formation and vessel occlusion in tumor vessels by blocking thrombin-induced EC activation and vascular endothelial growth factor-A (VEGF-A)-mediated VWF release. Intradermal tumor cell inoculation in VWF- and ADAMTS13-deficient mice did not alter lymph node metastases compared with wild type animals. Interestingly, multiple tumor-free distal organs exhibited hallmarks of malignancy-related VTE, including luminal VWF fibers, platelet-rich thrombi and vessel occlusions. Furthermore, ADAMTS13 deficiency, characterized by prolonged intraluminal VWF network lifetimes, resulted in a severely increased number of metastatic foci in an experimental model of hematogenous lung seeding. Treatment with Tinzaparin inhibited tumor-induced release of VWF multimers, impeded platelet aggregation and decreased lung metastasis. Thus, our data strongly suggest a critical role of luminal VWF fibers in determining the occurrence of thrombosis and cancer metastasis. Moreover, the findings highlight LMWHs as therapeutic strategy to treat thrombotic complications while executing anti-metastatic activities.
Gesehen am 08.07.2019